“What Am I to do?” – On Career Counsellor’s Dilemmas - Cardoso, Paulo (2016)
In this study, we explored main dilemmas psychologists face in career counselling in two main professional settings: employment and education. Participants included 24 experienced Portuguese psychologists, working in employment (n = 14) and educational (n = 10) settings. We used consensual qualitative research to conduct and analyse semi-structured interviews. Results revealed dilemmas’ in ﬁve domains: neutrality, assessment, dual loyalty, role boundaries, and conﬁdentiality, with the typical dilemma in the domain of neutrality. Differences between groups were found in the domains of dual loyalty and role boundaries